Pro SQL Server 2022 Administration A Guide for the Modern DBA - Carter, Peter A. (ITpro collection, 2022)
Get your daily work done efficiently using this comprehensive guide for SQL Server DBAs that covers all that a practicing database administrator needs to know. Updated for SQL Server 2022, this edition includes coverage of new features, such as Ledger, which provides an immutable record of table history to protect you against malicious data tampering, and integration with cloud providers to support hybrid cloud scenarios. You'll also find new content on performance optimizations, such as query pan feedback, and security controls, such as new database roles, which are restructured for modern ways of working. Coverage also includes Query Store, installation on Linux, and the use of containerized SQL. Pro SQL Server 2022 Administration takes DBAs on a journey that begins with planning their SQL Server deployment and runs through installing and configuring the instance, administering and optimizing database objects, and ensuring that data is secure and highly available. Readers will learn how to perform advanced maintenance and tuning techniques, and discover SQL Server's hybrid cloud functionality. This book teaches you how to make the most of new SQL Server 2022 functionality, including integration for hybrid cloud scenarios. The book promotes best-practice installation, shows how to configure for scalability and high availability, and demonstrates the gamut of database-level maintenance tasks, such as index maintenance, database consistency checks, and table optimizations. What You Will Learn Integrate SQL Server with Azure for hybrid cloud scenarios Audit changes and prevent malicious data changes with SQL Server's Ledger Secure and encrypt data to protect against embarrassing data breaches Ensure 24 x 7 x 365 access through high availability and disaster recovery features in today's hybrid world Use Azure tooling, including Arc, to gain insight into and manage your SQL Server enterprise Install and configure SQL Server on Windows, Linux, and in containers Perform routine maintenance tasks, such as backups and database consistency checks Optimize performance and undertake troubleshooting in the Database Engine Who This Book Is For SQL Server DBAs who manage on-premise installations of SQL Server. This book is also useful for DBAs who wish to learn advanced features, such as integration with Azure, Query Store, Extended Events, and Policy-Based Management, or those who need to install SQL Server in a variety of environments.